2016
DOI: 10.21767/2254-6081.100064
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Quality of Life among Women Aged 35-55 Suffering from Breast Cancer

Abstract: Background: Breast cancer is the most common type of cancer with women worldwide, striking more and more at women in productive age of life, and the success of healthcare for women with this disease is measured with the quality of life of survivors. The aim of this study was to examine how the breast cancer affects the quality of life of women aged 35-55 and in what dimension of health quality of life is the least accomplished.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Jaiyesimi et al in their study reported that, compared to other areas of functioning, social was the most affected [11]. Similarly, Zivana et al found that emotional and social domains scores were significantly lower [10]. The mean SD score found in the physical domain in this study is comparable to the score of 53.45+/-16.2 reported by Marco et al in the study of quality of life among breast cancer survivors for the same parameter using the same instrument [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jaiyesimi et al in their study reported that, compared to other areas of functioning, social was the most affected [11]. Similarly, Zivana et al found that emotional and social domains scores were significantly lower [10]. The mean SD score found in the physical domain in this study is comparable to the score of 53.45+/-16.2 reported by Marco et al in the study of quality of life among breast cancer survivors for the same parameter using the same instrument [20].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, some domains of QOL are more affected than others. Gavric et al in Bosnia reported that emotional and social domains were the most significantly affected domains of QOL [10]. Whereas a local study on health-related QOL and its determinants reported that the impairment in overall QOL was significant in physical, cognitive, and social domains [11].…”
Section: Introductionmentioning
confidence: 99%